2007
DOI: 10.4269/ajtmh.2007.77.571
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Acute Diarrhea in Children and Adults in Tunis, Tunisia, with Emphasis on Diarrheagenic Escherichia coli: Prevalence, Phenotyping, and Molecular Epidemiology

Abstract: A total of 271 stool specimens were collected from children (diarrheagenic, n = 115 and control, n = 54) and adults (diarrheagenic, n = 73 and control, n = 29) from Tunis, Tunisia, and processed to detect bacterial enteropathogens, parasites, and viruses. Diarrheagenic Escherichia coli (DEC) were identified by their virulence genes (polymerase chain reaction) and adherence patterns (tissue culture assays). The most frequently isolated enteric pathogens from diarrheagenic children were enterotoxigenic E. coli (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
73
4
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 31 publications
15
73
4
4
Order By: Relevance
“…A significant association of EAEC with diarrheic children one year of age or younger compared with diarrheic children older than one year of age (p < 0.03) was observed as part of this study. Al-Gallas et al in Tunisia reported similar findings [27]. Substantial proportions of DEC were isolated from breastfed children (76.5%) in this study.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…A significant association of EAEC with diarrheic children one year of age or younger compared with diarrheic children older than one year of age (p < 0.03) was observed as part of this study. Al-Gallas et al in Tunisia reported similar findings [27]. Substantial proportions of DEC were isolated from breastfed children (76.5%) in this study.…”
Section: Discussionsupporting
confidence: 77%
“…In the present work, only EPEC, ETEC, and EAEC were detected in stool samples, with only EAEC being significantly found in diarrheic children (30.7%) compared with controls (9.3%) (p < 0.01). Compared with our findings, lower prevalence rates of EAEC from diarrheic children have been reported from Iraq (8%), Kuwait (2.6%), Libya (4.1%), and Tunisia (11.3%) [24][25][26][27].…”
Section: Discussioncontrasting
confidence: 51%
“…A low number of parasitic infections have been described in studies of the aetiology of diarrhoea in the Maghreb area (Al-Gallas et al, 2007). This low prevalence was confirmed in our series, in which only two parasitic infections (G. intestinalis, Entamoeba histolytica) were detected, being lower than that observed in a previous study performed in the same hospital with identical methodologies, in which a total of 10 G. intestinalis isolates were detected in a series of 63 children (15.9 %) with stature-ponderal delay (Oudaïna et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although some data on the aetiological causes of diarrhoea in some North African countries are available (Al-Gallas et al, 2007;Hassine-Zaafrane et al, 2011SdiriLoulizi et al, 2009SdiriLoulizi et al, , 2011, little is known about the aetiology and epidemiology of diarrhoea in Morocco. The latest estimates suggest that diarrhoea may be responsible for the death of 36 per 1000 live births annually in Morocco (UNICEF/WHO, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Diarrhea is defined as an intestinal disorder characterized by abnormal fluidity and frequency of faecal evacuations, usually at least three times in a 24-hour period. Bloody diarrhea refers to any diarrhea episode in which the loose or watery stools contain visible red blood [1][2][3]. Compared with watery diarrhea, bloody diarrhea generally lasts longer, associated with more complications, more likely to adversely affect a child's growth, and has a higher case fatality rate [2][3][4].…”
Section: Introductionmentioning
confidence: 99%